ChemInform Abstract: Copper‐Catalyzed Regioselective Hydroboration of Terminal Alkynes in Aqueous Medium. Issue 27 (16th June 2016) - Yao, Zi‐Jian; Hong, Shibin; Zhang, Wei; Liu, Mengyan; Deng, Wei
Abstract: The regioselectivity of the hydroboration reaction is significantly influenced by the alkyne substituent.